18-Fluorodeoxyglucose positron emission tomography in the diagnosis of prosthetic aortic graft infection: the difference between open and endovascular repair. (17th November 2022) - Tsuda, Kazumasa; Washiyama, Naoki; Takahashi, Daisuke; Natsume, Kayoko; Ohashi, Yuko; Hirano, Masahiro; Takeuchi, Yuki; Shiiya, Norihiko
Abstract: OBJECTIVES: 18-Fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) has been reported as useful for diagnosing aortic graft infection. However, 18F-FDG uptake may depend upon various factors including open versus endovascular repair and time from surgery. We aimed to elucidate the factors influencing its uptake and the diagnostic value of 18F-FDG PET/CT after open and endovascular repair. METHODS: Hospital database of PET/CT ( N  = 14 490) and our departmental database were cross-checked to identify those who underwent 18F-FDG PET/CT after aortic repair. Patient's data were retrieved from the chart. Images were reviewed by 2 nuclear medicine specialists in consensus, and the presence of increased 18F-FDG uptake was recorded. The maximum standardized uptake value (SUV max) was measured. RESULTS: Among the 1112 patients who underwent aortic repair between 2011 and 2022, 71 patients were identified. Eighteen patients underwent 18F-FDG PET/CT for suspected graft infection and the remaining 53 patients for other purposes (malignancy, etc.). Fourteen patients were treated as aortic graft infection. They had significantly higher SUV max than those without graft infection [mean 8.64 (standard deviation 2.78) vs 3.40 (standard deviation 0.84); P  < 0.01]. In the non-infected grafts, SUV max was higher early after open surgical repair, while it remained low after endovascular repair. CONCLUSIONS: After endovascular aortic repair, a constant cut-off value of 'SUV max = 4.5' seems appropriate for diagnosing graft infection, since it remains low and stable from the early postoperative period. After open surgical repair, it seems acceptable to have 'stepwise cut-off value' depending on the time from surgery. Abstract : Prosthetic aortic graft infection is disastrous, requires surgical reintervention and is frequently difficult to diagnose [1].